Remap-GI : A Learning Model to Enhance Students’ Science Process Skills and Biology Cognitive Learning Outcomes - Ikramina Yusti Amina; Siti Zubaidah; Abdul Gofur; Azizul Ghofar Candra Wicaksono (Graduate School of Universitas Negeri Malang, 2022)
Abstract: The purpose of this study is to investigate the effects of the Remap-GI (Reading, Concept-Mapping, Group Investigation) learning model on students' cognitive learning outcomes and Science Process Skills (SPS). The Biology class at SMA Negeri 8 Malang was used as the research sample for the quasi-experimental research design over the course of 60 students in the 12th grade. This study used the blended learning-based Remap-GI learning model opposed to the GI (Group Investigation) learning model. SPS data were collected using non-test data (observation) and cognitive learning outcome variables in the form of multiple-choice questions. The Ancova test was used to analyze cognitive learning outcome variable data and SPS. The findings revealed that the blended learning-based Remap-GI learning model had an impact on SPS and cognitive learning outcomes. The Remap-GI learning model is based on blended learning as a learning model that can be used to improve SPS and students' cognitive learning outcomes, especially after the outbreak of the COVID-19 pandemic.